(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2026)
This article presents a comprehensive analysis of the genus Arthrophytum Schrenk (family Chenopodiaceae), which includes subshrub species adapted to arid regions of Eurasia and North Africa. The aim of the study is to summarize current scientific knowledge on the taxonomy, morphological characteristics, ecological adaptations, biogeographical distribution, and pharmacological potential of Arthrophytum species. Both modern scientific databases (SciFinder, Google Scholar, ScienceDirect, etc.) and traditional sources (botanical floras, herbarium collections, ethnobotanical reports) were used for data collection. Special attention is given to species with notable ecological plasticity and endemic distribution in Kazakhstan (A. iliense, A. balchaschense, A. pulvinatum, among others). The article concludes data from morphological, anatomical, and molecular analyses that have identified systematic status of several species, comprising the reorganization of A. balchaschense into the genus Haloxylon. Results of the pharmacognostic study of species A. schmittianum and A. scorparium are discussed, allocating their high biological activities such as antioxidant, antimitotic, neuroprotective, and antidiabetic activities. The outcomes show the significance of Arthrophytum as a main component of desert biodiversity and a perspective source of bioactive natural compounds. This review contains modern research gaps and summarizes the importance for future interdisciplinary studies, comprising preservation, sustainable use, and pharmacological studies of the genus. This article is useful for botanists, pharmacologists, ecologists, and medicinal plant experts, exploring plant and their life cycle in arid environments. Keywords: Arthrophytum, arid ecosystems, morphological adaptation, Amaranthaceae, bioactive compounds, antioxidant activity, ethnopharmacology, C4 photosynthesis, Central Asia flora, desert halophytes.